Effect of 5-HMF and furfural additives on bio-hydrogen production by photo-fermentation from giant reed. (March 2022) - Yang, Jiabin; Jiang, Danping; Shui, Xuenan; Lei, Tingzhou; Zhang, Huan; Zhang, Zhiping; Zhang, Xueting; Zhu, Shengnan; Zhang, Quanguo
Graphical abstract: Highlights: 5-HMF inhibited the nitrogenase activity in the process of PFHP. Low concentration of furfural increased the hydrogen production in PFHP. High concentrations of HMF and furfural inhibited the process of PFHP. Low concentration of furfural can increase the hydrogen production capacity of PSB. Abstract: Substances harmful to photo-fermentative biological hydrogen production (PFHP) were produced during cellulose hydrolysis. This study aimed to evaluate the effect of by-products (5-hydroxymethylfurfural (5-HMF) and furfural) released from lignocellulose during enzymatic hydrolysis process on PFHP. The exist of 5-HMF inhibited the hydrogen production. However, 0.2 g/L furfural improved the hydrogen production by 19 % compared to no addition (511.6 mL) with a maximum concentration of nitrogenase (109.96 IU/L) at 96 h. Furthermore, a 18.7 % enhancement of hydrogen production was also observed when 0.2 g/L 5-HMF and furfural were mixed at a ratio of 1:1, while decrement of hydrogen production at higher addition was observed as well. Through the scatter matrix analysis, it was concluded that 5-HMF and furfural additives had significant effects on PFHP. This study gave an insight into effect of lignocellulosic by-products on biohydrogen production.